«Im Kunstwerk lerne das Leben». Tradurre Hölderlin al tempo dell’ermetismo (Studia theodisca, 2019)
A comparative analysis of the translations into Italian of Hölderlin’s Andenken realized in the 1930s and 1940s by Vincenzo Errante, Gianfranco Contini, Diego Valeri and Leone Traverso shows how the translators recognized and adapted the poem’s poetic and formal innovations. The linguistic texture of the original, as well as peculiar philological and exegetical problems, forced the translators to reconceive their own definitions of poetry and style, and encouraged them to find new formal solutions which proved highly influential for contemporary Italian poets and intellectuals.